The tradition of foraging in Kalmyk and Tuvan folklore - Bakaeva, Elza Petrovna; Bayanova, Aleksandra Tagirovna; Kukanova, Viktoria Vasilevna (The New Research of Tuva, 2020)
This article is devoted to foraging as a type of economy specific for certain peoples of Central Asia. Ancestors of Tuvans and Oirats followed the “forest” type of economy, and their descendants must have preserved some of the foraging traditions. The authors aim to analyze the Kalmyk and Tuvan folklore for surviving traditions of foraging as an ancient type of Central Asian economy. The article also describes foraging-related details of traditional worldview. The study focuses on folklore texts of various genres, largely on fairy tales and epic. The ethnographic materials which contain descriptions of foraging are quite abundant. The study helped the authors arrive at a conclusion that although the folklore texts show only a few traces of foraging, some do indeed survive. Tuvans have preserved more of them, while Kalmyks both changed their climatic zone (from taiga to the steppe) and migrated far away from their ancestral lands, from Central Asia to the Lower Volga. This is the factor which must have removed most of the mentions of the old type of economy. Tuvan folklore features some of the archaic traditions of foraging which the texts link to primitive society and the cultural heroes of the folklore traditions. Foraging is usually associated with female characters, and gathering plants for men was a reproachable activity, allowed only under special circumstances. Later foraging became typical for the poorest part of the population. Kalmyk folklore texts feature a plot of a staying in archaic conditions in the original world, with its typical features, such as the scarcity of food, the ‘wagon of grass’, the reprobate state, or lack of social recognition. Characters had to cross the border between the original world and the social world in order to take up cattle breeding to achieve welfare and happiness. In the folklore texts containing information on primeval hunting and foraging, welfare is linked to the domestication of animals, which reveals the influence of the values of Kalmyk and Tuvan culture.